2013
DOI: 10.1001/jamaophthalmol.2013.778
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cytotoxic and Invasive Pseudomonas aeruginosa and Clinical Outcomes in Bacterial Keratitis

Abstract: To determine whether cytotoxic and invasive Pseudomonas aeruginosa strains differentially influence clinical presentation, outcomes, or therapeutic response in bacterial keratitis.Methods: Pseudomonas aeruginosa isolates from the National Eye Institute-funded Steroids for Corneal Ulcers Trial were subtyped as cytotoxic or invasive strains. The main outcome measure compared between the 2 subtypes was change in visual acuity at 3 months using Huber robust regression, adjusting for topical corticosteroid treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 36 publications
4
47
2
3
Order By: Relevance
“…These differences translate into various severities of disease; in mouse keratitis studies where infection is induced by cytotoxic strains, disease pathology is worse than that caused by invasive strains (3). Consistent with these findings, patients infected with cytotoxic strains have experienced more severe pathology and, consequently, suffered from greater visual impairment after recovery from infection (4). The immune response to both invasive and cytotoxic strains is dominated by dense neutrophil infiltrates, yet the infiltration pattern and responses of polymorphonuclear neutrophils (PMNs) differ depending on the type of strain.…”
mentioning
confidence: 71%
“…These differences translate into various severities of disease; in mouse keratitis studies where infection is induced by cytotoxic strains, disease pathology is worse than that caused by invasive strains (3). Consistent with these findings, patients infected with cytotoxic strains have experienced more severe pathology and, consequently, suffered from greater visual impairment after recovery from infection (4). The immune response to both invasive and cytotoxic strains is dominated by dense neutrophil infiltrates, yet the infiltration pattern and responses of polymorphonuclear neutrophils (PMNs) differ depending on the type of strain.…”
mentioning
confidence: 71%
“…13,16 Angus et al 38 reported a role for ExoS of P. aeruginosa in survival of the corneal epithelium. In clinical cases, Borkar et al 39 investigated 101 clinical cases of P. aeruginosa keratitis from the Steroids for Corneal Ulcers Trial, involving subtyping invasive or cytotoxic strains. They reported that infiltrate sizes in cases caused by invasive strains were larger than cases caused by cytotoxic strains.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested thatpseudomonas keratitis caused by invasive strains had better visual acuity than ones caused by cytotoxic strains. On the other hand, invasive ulcers are less significantly improved compared to cytotoxic ones at three months [27].…”
Section: Epidemiology P Aeruginosa Keratitismentioning
confidence: 93%
“…In some resistant cases, a combination of piperacillin/tazobactam may be useful [27]. The use of topical steroids (prednisone phosphate) combined with moxifloxacin did not improve the overall clinical outcome as showed in a multi-center clinical study that enrolled patients from India and USA [42].…”
Section: Management Of P Aeruginosa Keratitismentioning
confidence: 94%
See 1 more Smart Citation